2007
DOI: 10.1111/j.1365-2486.2007.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Large losses of soil C and N from soil profiles under pasture in New Zealand during the past 20 years

Abstract: The conversion of two-thirds of New Zealand's native forests and grasslands to agriculture has followed trends in other developed nations, except that pastoral grazing rather than cropping dominates agriculture. The initial conversion of land to pasture decreased soil acidity and elevated N and P stocks, but caused little change in soil organic C stocks. However, less is known about C and nutrient stock changes during the last two decades under long-term pastoral management. We resampled 31 whole soil profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
115
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 27 publications
6
115
5
Order By: Relevance
“…As a result, the magnitude of soil carbon (C) and nitrogen (N) pools could be altered by reallocating C and N between roots and shoots, or by recycling C and N through the animal excreta pathway (Hamilton and Frank 2001;Ruess and Mcnaughton 1987). Soil C stock has been shown to decrease significantly in temperate grassland during 20 years of grazing, which might be owing to loss from respiration (Schipper et al 2007). However, another analysis found that C stock was unchanged in grazed tussock grassland and increased in grazed hill country soil (Schipper et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the magnitude of soil carbon (C) and nitrogen (N) pools could be altered by reallocating C and N between roots and shoots, or by recycling C and N through the animal excreta pathway (Hamilton and Frank 2001;Ruess and Mcnaughton 1987). Soil C stock has been shown to decrease significantly in temperate grassland during 20 years of grazing, which might be owing to loss from respiration (Schipper et al 2007). However, another analysis found that C stock was unchanged in grazed tussock grassland and increased in grazed hill country soil (Schipper et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cultivation also removed ecosystem N due to crop consumption and export. Schipper et al (2007) indicates that significant amount of soil C and N is lost from soils under pasture in New Zealand during 20 years time period. Therefore it is expected that regrowing forest would very likely be nitrogen limited.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability and profitability of rangelands is largely a function of forage quality and quantity (Briske et al 2011). However, these ecosystems have, to varying degrees, experienced degradation of vegetation and soils due to overgrazing, plant invasions, and climate change (Asner et al 2004, Schipper et al 2007, Bai et al 2008. Thus, management practices aimed at enhancing plant production may have considerable potential to restore or increase grassland C storage and feed back on the global C cycle (Schimel et al 1990, Conant et al 2001, Follett 2001, Schuman et al 2002, Derner and Schuman 2007.…”
Section: Introductionmentioning
confidence: 99%